On some new generalized sequence spaces - Bektas, CA (Academic Press Inc Elsevier Science, 2003)
In this paper we define the sequence sets l(infinity) (u, Delta(2), (p)), c (u, Delta(2), p) and C-0 (u, Delta(2), p), and give alpha- and beta-duals of these sets. Further we investigate matrix transformations in the spaces and give a characterization of the class (l(infinity) (u, Delta(2), p), linfinity). (C) 2003 Elsevier Science (USA). All rights reserved.
Keywords: difference sequences; alpha- beta-duals